Significance of non-steroidal anti-inflammatory drugs in the prevention and treatment of cervical cancer - Xun Kan; Zhenhuan Zhou; Lianlian Liu; Reziwanguli Aiskikaer; Yinggang Zou (Heliyon)
Cervical cancer, ranking as the fourth most common cancer in women globally, is closely linked to chronic inflammation resulting from persistent human papillomavirus (HPV) infection. Chronic inflammation mediated by cyclooxygenase (COX) has been identified as a factor in cancer onset and progression, with HPV oncoproteins E6 and E7 inducing COX activation. Nonsteroidal anti-inflammatory drugs (NSAIDs) have demonstrated the capability to significantly inhibit COX activity, playing a crucial preventive and therapeutic role in various tumors. This paper explores the therapeutic value and potential clinical applications of NSAIDs in cervical cancer by examining the mechanistic interactions between HPV and COX and the carcinogenic effects of COX in cervical cancer.